Variation in assessing the need for change of snacking habits in schoolchildren’s oral health counselling - KIRSTI KASILA (IAPD and Blackwell, 2008)
Schoolchildren’s dietary behaviour, as related to oral health and practices of oral health counselling, requires special attention. Despite a decreasing trend, schoolchildren’s dental caries has not been eradicated 1 . Dietary factors have been found to influence schoolchildren’s oral health. There is convincing evidence for an association of the frequency and amount of sugar intake and dental caries 2,3 . According to a recent report, the consumption of soft drinks has increased in the past few decades. Currently, about 30% of schoolchildren consume them daily in the many countries studied.